Electricity Production from Yeast Wastewater in Membrane-Less Microbial Fuel Cell with Cu-Ag Cathode - Barbara Włodarczyk; Paweł P. Włodarczyk (Energies, 2023)
Wastewater has high potential as an energy source. Therefore, it is important to recover even the smallest part of this energy, e.g., in microbial fuel cells (MFCs). The obtained electricity production depends on the process rate of the electrodes. In MFC, the microorganisms are the catalyst, and the cathode is usually made of carbon material (e.g., with the addition of Pt). To increase the MFC efficiency (and reduce costs by reducing use of the noble metals), it is necessary to search the new cathode materials. In this work, the electricity production from yeast wastewater in membrane-less microbial fuel cells with Cu-Ag cathode was analyzed. In the first place, the measurements of the stationary potential of the electrodes (with Cu-Ag catalyst obtained by the electrochemical deposition technique) were performed. Because the cathode is constantly oxidized during the operation of ML-MFC, it was necessary to pre-oxidize the cathodes. Without pre-oxidation, there is a risk of changing the catalytic properties of the electrodes (along with the level of oxidation of the cathodes’ surface) throughout their operation in the ML-MFC. These measurements allowed to assess the oxidation activity of the Cu-Ag cathodes. Additionally, the influence of anodic charge on the catalytic activity of the Cu-Ag cathodes was measured. Next, the analysis of the electric energy production during the operation of the membrane-less microbial fuel cell (ML-MFC) fed by process yeast wastewater was performed. The highest parameters (the power of 6.38 mW and the cell voltage of 1.09 V) were obtained for a Cu-Ag catalyst with 5% of Ag, which was oxidized over 6 h, and after 3 anodic charges. This research proved that it is feasible to obtain the bio-electricity in the ML-MFC with Cu-Ag cathode (fed by yeast wastewater).